A note on the antibiotic properties of Bacillus subtilis against Colletotrichum trifolii - Douville, Y.; Boland, J.G. (Phytoprotection)

(untitled) (Société de protection des plantes du Québec (SPPQ)l, 1992)
The influence and mechanisms of action of Bacillus subtilis on Colletotrichum trifolii, a causal agent of anthracnose of alfalfa (Medicago sativa), were studied in vivo and in vitro. In growth room conditions, a cell-free culture filtrate of B. subtilis significantly reduced disease incidence and severity on alfalfa seedlings from 56% to 16% and from 2.0 to 1.2, respectively. Treatment of seedlings with washed cell suspensions of B. subtilis had no influence on disease. Applications of crude filtrate on alfalfa leaflets inoculated with C. trifolii were associated with reduced germination of conidia, lysis of conidia, and reduced formation of appressoria. Under in vitro conditions, crude filtrate reduced germination of conidia, and induced lysis of conidia and the formation of inflated germ tubes on germinating conidia. An antibiotic of the iturin family, iturin D, was tentatively identified as the active compound responsible for the suppressive effect of B. subtilis on C. trifolii.